Actualization of Civic Literacy in the Learning of Citizenship in High School - Anditasari, Rizqi Dian; Sutrisno, Sutrisno; Nur’aini, Khoirunnisa Nabila; Aristyowati, Andella (International Journal of Educational Qualitative Quantitative Research, 2023)
Citizenship literacy is an essential thing in shaping the character of students. The low literacy of students regarding civic literacy will have a significant impact and cause various national problems. This study aims to determine the actualization of civic literacy in the learning process of citizenship education in schools. Qualitative research methods with a case study approach. Data collection techniques with observational interviews, notes, and documentation as the primary source of information. The research was conducted at SMA N 1 Babatan, Ponorogo, Indonesia. The results of this study indicate that the actualization of civic literacy in learning citizenship education is carried out through several learning approaches, including 1) the learning model is applied to support the student's understanding process through citizen project activities. 2) Students are asked to discuss citizenship issues with the problem-solving system, then students are asked to write them down in the form of a resume. 3) democratic practice activities in the form of selecting student council presidents as a means of learning citizenship. 4) literacy program 20 minutes before learning. Before entering class, students read books for one hour, be it learning packages, novels, term papers, etc. 5) giving assignments regarding civic insight. This research contributes to improving the quality of civics learning and providing motivation.